Formulation of Theophylline Sustained-Release Tablets with a Combination of Eudragit RS 100 and Lactose - Trisnaningtyas, Meysiska; Ikasari, Endang Diyah; Intan Martha Cahyani (Journal of Food and Pharmaceutical Sciences, 2026)
Sustained-release (SR) delivery of Theophylline is pharmaceutically essential due to its narrow therapeutic index and the need to maintain controlled plasma exposure. This study aims to investigate the release kinetics and matrix-modifying roles of Eudragit RS 100 and lactose in three SR tablet formulations of Theophylline. Tablets were produced with the wet granulation method and evaluated for physicochemical properties, dissolution behavior according to USP specifications, and kinetic model fitting. The physicochemical evaluation revealed clear differences among formulations. F-1 exhibited the highest hardness (10.48 ± 0.10 kg/cm²) but excessive friability (2.40 ± 0.01%), whereas F-2 and F-3 showed lower hardness values (8.25 ± 0.03 and 8.03 ± 0.02 kg/cm²) with acceptable friability (0.32 ± 0.03% and 0.34 ± 0.03%). Granule flow properties improved progressively from F-1 to F-3, as indicated by reduced Carr’s Index (16.17 ± 0.16 to 11.58 ± 0.32%) and Hausner Ratio (1.193 to 1.131), accompanied by increased flow rates (12.12 ± 0.03 to 14.48 ± 0.53 g/s) (p < 0.05). These physicochemical differences were reflected in dissolution behavior and drug-release kinetics, confirming the matrix-modifying effects of Eudragit RS 100 and lactose. Kinetic modeling demonstrated formulation-dependent release mechanisms: F-1 showed the highest correlation with the zero-order model (R² = 0.9858), suggesting a near constant drug-release rate, whereas F-2 exhibited the best fit to a second-order model (R² = 0.9635), indicating concentration-dependent release. In contrast, F-3 was optimally described by the Korsmeyer–Peppas model (R² = 0.9545), consistent with anomalous transport governed by combined diffusion and polymer relaxation.